Energy dissipation during a rockfall and mechanical response of an energy dissipation structure - Li, De-jie; Chen, Fu-xiang; Chen, Pei-shuai; Xiao, Jing (Frontiers in Materials, 2025)
In this study, we investigated the rockfall motion characteristics for varying rock sizes and the structural responses of steel pipes with and without energy dissipation components. Specifically, we conducted rockfall tests under three conditions: (1) an inclined steel pipe, (2) an inclined pipe with a horizontal segment for energy dissipation, and (3) inclined and horizontal steel pipes combined with baffles. The results revealed that the velocity of the rocks of different sizes was similar in the steel pipes without energy dissipation components. The energy dissipation was primarily due to the friction between the rock and the steel pipe, and the friction coefficient was independent of the rock size. The use of horizontal steel pipes effectively dissipated the kinetic energy and reduced the rock velocities by an average of 72.23%. However, as the rock size increased, the velocity increased accordingly, resulting in reduction of the energy dissipation effect. The addition of baffles in the steel pipes increased the energy dissipation during the rockfall and decreased the rock velocity and the impact stress on the horizontal steel pipes. Compared to the single-baffle condition, the average impact stress on the horizontal steel pipes was reduced by 26.5% and 59.6% under the two-baffle and three-baffle conditions, respectively.